2020
DOI: 10.14574/ojrnhc.v20i1.626
|View full text |Cite
|
Sign up to set email alerts
|

COVID - 19 and Rural Health Care: Editorial

Abstract: Nurses have long been educated about the need to prepare for a possible future pandemic, it seems the future is now. During times of public health or natural disasters people who have the resources have historically fled cities to more rural locations. With this highly contagious COVID -19 virus, rural area health resources may soon be stretched to the limit. Meit, Kennedy, and Briggs (2007) wrote about the potential rural population surge during a future pandemic scenario and the problems the burdens this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…In this study, rural nurses with prior disaster nursing education showed higher disaster nursing competencies than their counterparts without prior education. These results are consistent with the findings of Jang et al (2022) Discussing the result of the current study on higher disaster nursing competencies among rural nurses with prior education on the related field, prior research shows that, conventionally, the nursing staff pool tends to be smaller in rural than in urban areas, and the same often occurs regarding the difficulty to attract and to retain nurses (Fahs, 2021). Further, efforts to recruit and to retain newly graduated nurses in rural areas have generally emphasized nursing managerial support and situational learning as advantages (Lea & Cruickshank, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, rural nurses with prior disaster nursing education showed higher disaster nursing competencies than their counterparts without prior education. These results are consistent with the findings of Jang et al (2022) Discussing the result of the current study on higher disaster nursing competencies among rural nurses with prior education on the related field, prior research shows that, conventionally, the nursing staff pool tends to be smaller in rural than in urban areas, and the same often occurs regarding the difficulty to attract and to retain nurses (Fahs, 2021). Further, efforts to recruit and to retain newly graduated nurses in rural areas have generally emphasized nursing managerial support and situational learning as advantages (Lea & Cruickshank, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…The literature shows that there is an incorrect bias that infectious diseases, such as COVID-19, are less likely to spread through rural areas compared with urban areas (Fahs, 2021). Since rural areas can suffer more serious damage from health-related problems owing to their less resourced healthcare delivery system (Fahs & Rouhana, 2020), and rural nurses are pivotal to the correct functioning of these systems, it is easy to rationalize how the improvement of their disaster nursing competencies is crucial for healthcare delivery in rural and remote areas.…”
Section: Discussionmentioning
confidence: 99%